Anti bacterial activity of pyranocoumarins and crude extracts of Calophyllum symingtonianum - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher (2014)
The genus Calophyllum which belongs to Guttderae family is known as ‘bintangor’ by Malay local folks. Previous phytochemicals studies on several Calophyllum species successfully isolated group of pyranocoumarins. In this study, a phytochemical analysis of C. symingtonianum M. R. Hend & Wyatt-Sm. was conducted involving stem barks, leaves and heartwood. Cold extraction method was employed by using dichloromethane and methanol to give the respective crude extracts. Two pyranocoumarins were successfully isolated from stem bark dichloromethane crude extract identified as inophyllum D and isocordato-oblongic acid. Screening on their antibacterial activities were evaluated against B. subtilis, S. aureus, P. aeruginosa, P. putida and E. coli by using disc diffusion (DD), minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) methods. The MBC values showed only the methanol stem bark crude extract inhibited P. aeruginosa and E. coli growth each at 225 ug/mI. The methanol heartwood crude extract moderately inhibited the growth of S. aureus, P. aeruginosa and P. putida each at 450 ug/mL.